Artificial intelligence and e-contracts: A study - Kumar, Ravinder (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
E-contracting has revolutionized modern business by streamlining and speeding up the contracting process, turning what traditionally took months into a matter of days or hours. Advances in artificial intelligence (AI) and widespread use of the Internet have greatly facilitated this transformation. E-contracts comply with all required legal requirements and transform traditional paperwork into a digital format, enabling seamless transactions in global markets. The advent of econtracts has simplified purchasing processes, allowing consumers to order, cancel, return products and make warranty claims online with unprecedented ease. This flexibility transcends geographical boundaries, making both national and international transactions more simple and efficient. AI plays a key role in this new paradigm by providing tools that can review and manage large volumes of contracts faster and more accurately than human capabilities. The integration of AI into e-contracts has introduced new dimensions to contract management, including the ability for AI systems to enter into contracts autonomously, a previously unimaginable concept. This development has sparked discussion over the future legal status of AI in contract law. Despite ongoing debates, the role of AI in contracting is increasingly being recognized, with new standards emerging to address the unique challenges and benefits it brings. Major online marketplaces such as Amazon, Flipkart and Alibaba exemplify the practical application of econtracts, providing users with a straightforward and efficient means to purchase goods and services. Ease of use, instant confirmation, and comprehensive post-purchase support, including cancellations and returns, highlight the significant improvements that AI and the Internet have brought to the contracting process. The integration of AI and e-contracts has fundamentally changed the way contracts are formed, executed and managed. This technological advancement delivers increased efficiency, accessibility, and reliability in modern business transactions, underscoring the profound impact AI will have on the future of contract law and commerce.